Conditional Sentences in English and Their Problems for First Year Students of Faculty of Cultural Sciences, Universitas Gadjah Mada - , HERNITA RATNA AULIA; , Drs. Adi Sutrisno, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research focuses on the studentsâ problem in using conditional sentences. It covers the type of conditional sentences which constitutes the common mistake, the problems which the students have, and the understanding level of the students. The subjects of research are first year students of Faculty of Cultural Sciences, Universitas Gadjah Mada. All of the subjects were considered in the same level of English proficiency. To gain the data, the writer used instruments which include a test and questionnaire. Based on the result of the test, the percentages of mistake are 29,06% in type 1, 35,92% in type 2, and 35,02% in type 3. Therefore, conditional sentence type 2 is the common mistake for the students. Based on the result of questionnaire, the biggest problem which the students have is the use of each type of conditional sentences. Overall, the percentage of the understanding level is 55,83%. Thus, it is obvious that the students have difficulties in acquiring conditional sentences.